Pinch point determination and Multi-Objective optimization for working parameters of an ORC by using numerical analyses optimization method - Kocaman, Emrullah; Karakuş, Cuma; Yağlı, Hüseyin; Koç, Yıldız; Yumrutaş, Recep; Koç, Ali (Energy conversion and management, 2022)
•An ORC for a reheat furnace by considering all constructional limitations and restrictions was designed.•An analytical mathematical model for designing ORC that considers all system limitations was introduced.•A multi-objective optimisation design procedure and numerical analysis method for deciding optimal pinch point temperature for the ORC was developed.•Easily understandable and re-calculatable pinch point deciding and multi-objective optimisation mathematical model procedure was proposed.•A mathematical design and optimisation methodology which is compatible with all organic working fluids and working conditions was presented. In parallel with Kyoto, Paris and the green production agreements, the nowadays crucial subject is minimising energy consumption, increasing renewable energy usage and recovering waste heat. When it comes to waste heat, the organic Rankine cycle (ORC) technology comes fore. However, although the presence of many studies on the ORC in the literature, there is still an intense gap related to information on ORC working conditions, pinch point detection and numerical design and analysis methods. In this respect, the present paper suggests a multi-objective optimization model for an ORC by considering many parameters that affect the performance of the ORC like fluid type, thermodynamic properties of the organic fluids, pinch point temperature etc. For the analyses, experimentally recorded exhaust gas parameters for a reheat furnace located in the iron and steel plant were used. By considering all these, all performance-affecting parameters were included through the development of the multi-objective model. For the analyses, two wet types (ethanol, methanol), two isentropic (acetone, butene), and two dry types (cyclohexane, benzene) working fluids were selected to develop the multi-objective design and optimising method. After comprehensive analyses, it was seen that the developed mathematical model was valid for the designing and analysing of the ORC. In addition, it was observed that the system performance increases as the pinch point temperature difference decreases. In addition, it was seen that isentropic fluids have low efficiency in medium-temperature heat sources. Considering the system performance, initial investment cost and payback periods, it was seen that a waste heat recovery plant using Benzene, Methanol and Ethanol as working fluids is more feasible.